Efektivitas Model Pembelajaran Case Based Learning Berbantuan Google Earth terhadap Hasil Belajar Geografi Siswa SMA - Ida Bagus Gede Sanjaya Putra Wanashara; I Putu Sriartha; I Gede Putu Eka Suryana (DIAJAR: Jurnal Pendidikan dan Pembelajaran, 2026)
This study aims to analyze the effectiveness of the Case Based Learning (CBL) model assisted by Google Earth on students’ geography learning outcomes at SMA Negeri 2 Singaraja. This study employed a quantitative approach with a quasi-experimental design using a non-equivalent control group design. The research sample consisted of class X7 as the experimental class and class X10 as the control class, which were determined after an equivalence test and selected through random sampling. Data were collected through observation, learning outcome tests, and student response questionnaires. The test and questionnaire instruments were validated and tested for reliability before use. Data were analyzed using normalized gain scores, the Wilcoxon Signed Rank Test, the Mann-Whitney U Test, and Likert-scale questionnaire analysis. The results showed that the experimental class experienced a higher improvement in learning outcomes than the control class, with an N-Gain score of 44.10 in the experimental class and 5.04 in the control class. The Wilcoxon test indicated a significant difference between pretest and posttest scores in the experimental class, while the control class showed no significant difference. The Mann-Whitney test also showed a significant difference in learning outcome improvement between the two classes. In addition, students’ responses to the learning model were categorized as very good, with a percentage of 93.58%. Therefore, the Google Earth-assisted CBL model is moderately effective in improving students’ geography learning outcomes and can be used as an alternative innovative learning model for the topic of lithosphere dynamics.